Management the Potential Data on Web Site For Communicating Research In Social and environment Issues - Yendra, Rado (Indonesian Council of Premier Statistical Science, 2025)
This paper focus on Management the Potential Data On Web Site For Communicating Research In Social and Environment Field with a special focus to produce some research on education and climate issue. It discusses the potentials and challenges of Internet data for social and environmet and presents a selection of the relevant literature to establish the wide spectrum of topics, which can be reached. Such data represent a large and increasing part of everyday life, which cannot be measured otherwise. They are timely, perhaps even daily following the factual process, they typically involve large numbers of observations, and they allow for flexible conceptual forms and experimental settings. In this paper, the data from website be managed to produce some academic article. Internet data can successfully be applied to a very wide range of climate issues including forecasting (e.g. of rainfall, wind speed, and the like)  and detecting education issues  (e.g. spatial analysis for relation a number of male and female students and test score mathematic and foreign lenguages subjects) ,Our article reviews the current attempts in the literature to incorporate Internet data into the mainstream of scholarly empirical research and guides the reader through this Special Issue. We provide some insights and a brief overview of the current state of research.